Pengaruh Strategi Promosi Produk Menggunakan Facebook terhadap Keputusan Pembelian: Studi Kasus pada Unit Usaha Klinik Tani di Kelurahan Suryawangi - Nova Hari Santhi; Kholidatul Umam (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This research is entitled The Influence of Product Promotion Strategies Using Facebook on Purchasing Decisions (Case Study of the Tani Clinic Business Unit in Suryawangi Village). This research aims to determine the influence of product promotion strategies using Facebook on purchasing decisions (case study at the Tani Clinic Business Unit in Suryawangi Village). This research uses quantitative methods. The sample in this study was 96 respondents using a rating scale for two variables: Product Promotion (X) and Purchase Decision (Y). The research results show that the average score for variable X is 3.86 and for variable Y is 3.94, which indicates a good category. Data analysis using the t test shows a t value of 12,178 which is higher than t table 1,660 at a significance level of 0,000, so that the hypothesis H0 is rejected and H1 is accepted, indicating that there is a significant influence of product promotion on purchasing decisions. The correlation coefficient R is 0.612 and explains the percentage influence of the independent variable (product promotion) on the dependent variable (purchasing decisions) of 61.2% of the variation in purchasing decisions. The research results show that product promotion via Facebook has a positive and significant influence on purchasing decisions at the Tani Clinic, Suryawangi Village.